PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT - Endang Sri Utami (Jurnal Akuntansi, 2015)
Public accounting profession is a profession that is expected to put confidence as parties can conduct an audit of the financial statements and may be responsible for the opinion given. Of the public accounting profession, the public expects that assessment independent and impartial to the information presented by management companies in the financial statements. This research was conducted with the aim to obtain empirical evidence whether the factors ofcompetence, independence, professionalism, integrity auditor effect on audit quality. T-test results showed that the factors of competence, independence, professionalism auditors effect on audit quality. While factors do not affect the integrity of the auditors on audit quality. The coefficient of determination indicates that the factors of competence, independence, professionalism, integrity of the auditor is able to explain the quality of audits by 85 %, while the remaining 15%is explained by other variables that are not used in this study.